The Effect of Income Inequality on Ecological Footprint in Iran - Zana Mozaffari; Fatemeh Vaysi (اقتصاد باثبات)
Introduction: In general, the lack of balance in income distribution can have a negative impact on the environment in two different ways. On the one hand, individuals with higher incomes may excessively use natural resources and introduce more pollutants into the environment. On the other hand, individuals with lower incomes may have insufficient exploitation of natural resources due to lack of resources, which may lead to environmental degradation. Therefore, inadequate incomedistribution can lead to an inappropriate ecological footprint. This article examines the effect of income inequality on the ecological footprint in Iran using the GMM time series method over the period of 1990-2020.Methodology: For model estimation, the GMM time series econometric method was used because the model used in this study is dynamic and satisfies the generalized moment conditions. In fact, GMM is used for time series models that are linearand meet the conditions of generalized moments and ancillary properties. The use of this method for estimating models can have many advantages.Findings: The estimation results showed that the model's statistical indicators are in a satisfactory state. The null hypothesis of the Sargan test cannot be rejected, indicating that the instrumental variables used in the estimation model are valid. Given the logarithmic nature of the model, all the estimation coefficients reflect elasticity. The ecological footprint of the previous period had a positive and significant impact on the ecological footprint of the current period. Income inequality had a positive and significant impact on the ecological footprint, while the use of renewable energy had a negative and significant impact.Discussion and Conclusion: Ecological footprint is a comprehensive indicator of human pressures on the environment. Income inequality in the economy can have various effects on environmental quality, including its impact on social demand. Income inequality can affect economic and environmental behaviors by changing consumer preferences. Previous research in the Iranian economy has used greenhouse gas emissions such as carbon dioxide as a proxy for environmental destruction. Therefore, this study examines the effect of income inequality on the ecological footprint of Iran during the period of 1990-2020. Based on the results, environmental quality is influenced by previous period values, and a dynamic GMM time series model is used to examine this issue. The estimation results show that income inequality has a positive and significant impact on the ecological footprint. Income inequality distribution in a society can have profound effects on ecological footprint. For example, individuals with high incomes can make more purchases, which can lead to increased production, resource use, and environmental destruction.Income inequality can also lead to increased class and social diversity, and individuals with lower incomes may predominantly live in poorer and more vulnerable areas, which are likely to have poorer environmental conditions. Additionally, income inequality can create imbalanced decision-making in various areas, including environmental protection, due to unequal distribution of resources and power in society.Overall, income inequality can lead to increased environmental destruction, reduced natural resources, and increased income inequality.